SKRINING FITOKIMIA DAN AKTIVITAS ANTIBAKTERI in vitro EKSTRAK HEKSANA-PETROLEUM ETER Artemisia cina Berg. ex Poljakov - Elizabeth B.E Kristiani; Sri Kasmiyati; Maria Marina Herawati (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2015)
The objectives of this reserch were to determine the antibacterial activity of hexane-petroleum ether (1 : 1 v/v) extract of Artemisia cinaBerg. ex Poljakov on Escherichia coli and Staphylococcus aureus and its compounds. The design of the research was using completely Randomized Design in five concentration of extract that were 0, 50, 75, 100, 150, dan 200 mg/ml with four repliceted. Ethanol 60% was used as negative control and tetracycline as positive control. There were three steps of research. First step was extracted the plant using soxhlet method with hexane-petroleum ether (1:1 v/v). Second step was determined the antibacterial activity of hexane-petroleum ether (1:1 v/v) extract in various concentration of that extracts on E. Coli and S. aureus using agar diffusion method. Analysis of Variance (ANOVA) and was used to determined the significan different of diameter of inhibition between the treatments. Thirdsteps was phytochemical analysis of extract. The highest antibactrial activity on E. Coli was at 100 mg/ml whereas on S. Aureus at 150 mg/ml. That extract was contained flavonoid, alkaloid, essential oils, saponin, sterol, tritepene, hydrolized tannin, and coumarin.